Kegel Exercises For Perineal Wound Healing In Postpartum At The Driyorejo Gresik Health Center - Astutik, Reni Yuli; Mei Ringga Peni Santiana; Retno Palupi Yonni Siwi; Devi Putri Nursanti; Nining Istighosah (Universitas STRADA Indonesia, 2024)
Kegel exercises are exercises to strengthen the pelvic floor muscles, help prevent urinary incontinence problems, stretching the perineal tissue. The aim was to determine the effectiveness of Kegel exercises in healing perineal wounds in postpartum mothers at the Driyorejo Gresik Community Health Center. Methods used Pre-Experimental with One-Group Pretest-Posttest Design. Samples were 30 postpartum with perineal wound healing in the Driyorejo Gresik Health Center working area in March 2024. Respondents underwent a pre-test on day 1 and a post-test on 7 days postpartum. Data were collected using questionnaires and observation sheets using the REEDA score. Data analysis used Chi-Square test. The results showed that the mean of REEDA score pretest was 11.54 and posttest was 4.32. The result showed that there was a difference in REEDA scores before and after Kegel exercises (p=0.016). There was a difference in the perineal wound healing before and after Kegel exercises were given (p=0.007).